Impact of Lapindo Muds in Aquaculture Ponds on Periphyton Growth - Anugerah, Putri (Aquatic Life Sciences, 2024)
This study aimed to determine the abundance, diversity, and periphyton dominance in the pond using Lapindo mud that cultivated catfish of different sizes. The method used was descriptive quantitative, describing the relationship between the pool using Lapindo mud and fish cultivation of different sizes on the growth of periphyton on the walls of the pond. In this research, there were three different treatments: treatment A (100% Lapindo mud), treatment B (75% Lapindo mud), and treatment C (50% Lapindo mud). There were also three groups of catfish sizes: 4 cm, 6 cm, and 8 cm. The simple linear regression test showed that the age of the fish did not affect the growth of periphyton, while different concentrations of Lapindo mud influenced the growth of periphyton. In all ponds, the Cultivation Diversity Index was still relatively low. The results of periphyton diversity research in the polluted waters of Lapindo mud indicated the dominance index value and the highest abundance of Bacillariophyceae. The most common types of Bacillariophyceae were Amphora and Diatoma. The abundance of the genus indicate that they are easy to adapt to contaminated water areas.